Toxicity of chlorhexidine on odontoblast-like cells - Rosetti Lessa, Fernanda Campos [UNESP]; Fabio Aranha, Andreza Maria [UNESP]; Nogueira, Indri [UNESP]; Aparecida Giro, Elisa Maria [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2010)
Chlorhexidine gluconate (CHX) is recommended for a number of clinical procedures and it has been pointed out as a potential cavity cleanser to be applied before adhesive restoration of dental cavities. Objective: As CHX may diffuse through the dentinal tubules to reach a monolayer of odontoblasts that underlies the dentin substrate, this study evaluated the cytotoxic effects of different concentrations of CHX on cultured odontoblast-like cells (MDPC-23). Material and Methods: Cells were cultured and exposed to CHX solutions at concentrations of 0.06%, 0.12%, 0.2%, 1% and 2%. Pure culture medium (alpha-MEM) and 3% hydrogen peroxide were used as negative and positive control, respectively. After exposing the cultured cells to the controls and CHX solutions for 60 s, 2 h or 60 s with a 24-h recovery period, cell metabolism (MTT assay) and total protein concentration were evaluated. Cell morphology was assessed under scanning electron microscopy. CHX had a dose-dependent toxic effect on the MDPC-23 cells. Results: Statistically significant difference was observed when the cells were exposed to CHX in all periods (p<0.05). Significant difference was also determined for all CHX concentrations (p<0.05). The 60-s exposure time was the least cytotoxic (p<0.05), while exposure to CHX for 60 s with a 24-h recovery period was the most toxic to the cells (p<0.05). Conclusion: Regardless of the exposure time, all CHX concentrations had a high direct cytotoxic effect to cultured MDPC-23 cells.
Keywords: Chlorhexidine; Odontoblasts; Cytotoxicity; Cell viability; Protein synthesis